THE RELATIONSHIP BETWEEN PERCEPTIONS OF CAREER DEVELOPMENT MANAGEMENT AND TEACHERS’ ACHIEVEMENT MOTIVATION IN PURSUING PROMOTION - Selva Susila Oktoberia (World Psychology, 2026)
Career advancement through promotion represents a critical dimension of teachers’ professional development, yet many teachers show varying levels of motivation to pursue this process. These differences are often shaped by how teachers perceive the management of career development within their institutions. This study aims to examine the relationship between teachers’ perceptions of career development management and their achievement motivation in pursuing promotion. A quantitative correlational research design was employed using a cross-sectional survey approach. Data were collected from teachers through structured questionnaires measuring perceptions of career development management and achievement motivation related to promotion. The data were analyzed using descriptive statistics and inferential techniques, including correlation and regression analysis, to identify the strength and direction of the relationship between variables. The findings reveal a significant positive relationship between perceptions of career development management and teachers’ achievement motivation in pursuing promotion. Teachers who perceive career development management as transparent, supportive, and well-organized demonstrate higher levels of motivation to engage in promotion-related activities, while negative perceptions are associated with lower motivational levels. The study concludes that effective career development management plays a crucial role in fostering teachers’ achievement motivation toward promotion. Strengthening clarity, fairness, and institutional support in career management systems may enhance teachers’ motivation for professional advancement and contribute to sustainable teacher development.